Pengaruh Strategi Active Learning Tipe Index Card Match Terhadap Hasil Belajar Peserta Didik pada Pembelajaran Tematik Terpadu di Kelas III Sekolah Dasar - Sari, Rici Nofia; Amini, Risda (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2017)
This study aims to determine the effect of the index card type active learning strategy on student learning outcomes in integrated thematic learning. This type of research is quasi-experimental with nonequivalent control group design. The research was conducted in 15 ulu gadut in Padang.  The sampling technique is simple random sampling, which is selected as the sample class is class IIIC as the experimental class and class IIIA as the control class. Sampling is using purporsive sampling technique. The instrument used in this study was an essay test in the form of an essay. Based on the results of data analysis using t-test, obtained tcount = (2,58) > ttabel (2,010) at a significant level of 0.05 and dk = 48. It means that tcount > ttable, so H1 is accepted. Thus, there is a significant effect of index card macth type active learning strategy on the learning outcomes of integrated thematic in class III of Elementary School.